1988
DOI: 10.1177/002221948802100911
|View full text |Cite
|
Sign up to set email alerts
|

The Exclusionary Clause and the Disadvantaged: Do We Try to Comply with the Law?

Abstract: Among school psychologists serving a national, systematic sample of public schools, 47% reported compliance with Section 4 of the learning disabilities exclusionary clause, 38% reported purposeful noncompliance, and 10% reported inconsistent compliance. Those who attempt compliance consider a variety of factors in their decisions, but few pupils are actually excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Clinicians often ignore the exclusionary clause in the definition of LD, which prohibits categorizing a student as LD if the apparent difficulties are due to cultural or economic disadvantage (Fletcher & Navarrete, 2003). In fact, one survey of professionals revealed that fewer than 50% of school psychologists reg-ularly considered the exclusionary clause in their diagnosis, and 37% indicated that they usually ignored or tried to get around the clause (Harris, Gray, Davis, Zaremba, & Argulewicz, 1997). Finally, greater availability and specificity of services for children with disabilities is associated with lower prevalence and more specific diagnosis of LD, suggesting that misdiagnosis may serve the purpose of providing some kind of service to children in need (Shepard, 1983).…”
Section: Prevalence and Economic Issuesmentioning
confidence: 99%
“…Clinicians often ignore the exclusionary clause in the definition of LD, which prohibits categorizing a student as LD if the apparent difficulties are due to cultural or economic disadvantage (Fletcher & Navarrete, 2003). In fact, one survey of professionals revealed that fewer than 50% of school psychologists reg-ularly considered the exclusionary clause in their diagnosis, and 37% indicated that they usually ignored or tried to get around the clause (Harris, Gray, Davis, Zaremba, & Argulewicz, 1997). Finally, greater availability and specificity of services for children with disabilities is associated with lower prevalence and more specific diagnosis of LD, suggesting that misdiagnosis may serve the purpose of providing some kind of service to children in need (Shepard, 1983).…”
Section: Prevalence and Economic Issuesmentioning
confidence: 99%
“…It was indicated that less than 50% of those surveyed regularly tried to comply with the clause, and about 37% percent reported they routinely ignored or attempted to circumvent this procedural safeguard. From data gathered in this same study, it was reported that fewer than one-third of those sur veyed considered factors such as language, social history, and the cultural values of the student and their family in their deliberations leading to a diagnosis (Harris, Gray, Davis, & Zaremba, 1997).…”
Section: Problems In the Definition And Diagnosis Of Ldmentioning
confidence: 96%
“…It was indicated that less than 50% of those surveyed regularly tried to comply with the clause, and about 37% percent reported they routinely ignored or attempted to circumvent this procedural safeguard. From data gathered in this same study, it was reported that fewer than one-third of those surveyed considered factors such as language, social history, and the cultural values of the student and their family in their deliberations leading to a diagnosis (Harris, Gray, Davis, & Zaremba, 1997).…”
Section: Problems In the Definition And Diagnosis Of Ldmentioning
confidence: 97%